A new burner to characterize laminar diffusion flames generated from wildland fuels. (June 2020) - Severino, G.; Cabrera, A.; Contreras, J.; Pinto, P.; Cruz, J.J.; Fuentes, A.
Abstract: A new burner is presented, designed to generate laminar and axisymmetric diffusion flames from wildland fuels. This burner consists of a porous sample holder where wildland fuel elements are deposited. The sample holder is mounted on a cylindrical structure which allows an oxidizer coflow injection around the fuel samples. When the sample is ignited, a well-controlled flame is generated because the coflow surrounds the flame and prevents the formation of instabilities. This was proved with flame stability measurements in several scenarios where sample holder diameter, size distribution of the fuel and porosity of the sample were varied. Ignition of the fuel was achieved with ethanol. Two fuels were tested: Pinus radiata pine needles and Eucalyptus globulus leaves. Both fuels were cut and sieved into three size distributions. The CH∗ spontaneous and visible emission from the flame were detected in order to analyze the flame structure after the ethanol is consumed. The visible flame height decreased linearly with time after the ignition period, and as the oxidizer flow rate increased. Finally, deconvoluted soot pyrometry measurements at two wavelengths were performed in order to demonstrate the ability of the burner to generate stable and axisymmetric flames apt for non-intrusive diagnostics.